Transformative Approaches to Career-Ready Education - Gratchev, Ivan; Selvan, Krishnasamy T.; Espinosa, Hugo G. (Springer Nature Singapore : Imprint: Springer, 2025)
XVI, 241 p. 40 illus., 33 illus. in color.